Spin doctors : the chiropractic industry under examination - Benedetti, Paul (Dundurn Group, 2002)
Canadians visit chiropractors about 30 million times a year, and surveys show that patients are generally satisfied with their treatment. But studies also show that as many as two hundred Canadians a year suffer strokes brought on by neck manipulation. Spin Doctors takes a hard, dramatic, and spine-chilling look into the world of chiropractic medicine. You will be surprised to learn what chiropractors treat and why and how much it costs you as a taxpayer. Most importantly, you'll learn how to protect yourself and your family from dangerous adjustments, practice-building tactics, bogus treatmen.
Keywords: Chiropractic -- Evaluation.; Chiropractic -- Complications.; Chiropractic -- Canada.; Malpractice.; Quacks and quackery.; Chiropractic -- ethics; Chiropractic -- history; Malpractice; Manipulation, Chiropractic -- adverse effects; Quackery; Canada; Chiropratique -- Évaluation.; Chiropratique -- Complications et séquelles.; Chiropratique -- Canada.; Responsabilité professionnelle.; Charlatanisme.; malpractice.; MEDICAL -- Chiropractic.; Quacks and quackery; Chiropractic; Chiropractic -- Complications; Chiropractic -- Evaluation